تقويم وقياس العائد على الاستثمار في تدريب الموارد البشرية: بحث ميداني لعينة مختارة من الشركات العراقية الخاصة (Journal of Accounting and Financial Studies ( JAFS ), 2009)
The great challenge that will face the management in the developed and developing countries at the same time as core issue is represented in the question of the labor productivity in the field of in the Training Of human which is believed that it will prevail upon the jobs of their organization for many coming decades in in next years. Farther more, it will limit the construction of the communities and the quality of this life. Therefore, the priority of the economics of those countries will be headed toward increasing this productivity and giving it tried finally to control economically and managerially. In the light of information era, every organization should become knowledgeable enterprise. And for this reason, the achievement of such benefits in the productivity of services in companies to these achieved in productivity of goods. It supposes that the priority should be to developed world arena nowadays to the productivity in human sources. Unless it developed rapidly, the social and economical situations of that great groups of workers which their numbers become greater than the numbers of the workers working in the industry during its peak stage it will be declined or may become confused. In conclusion, the researcher identifies the weak points in Training Of human textile products, and could introduce some suggestions and recommendations to overcome. This would serve the producer and consumer and increase social and economic development.